Mental Health Care For Helpers: A Necessary Ingredient Of Trauma Recovery Training And Assistance In War Zones - Ajduković, Marina (Array, 1997)
Short-term, intensive group training which focused on mental health needs of care-providers who work daily with traumatized and distressed population, followed by supervision sessions proved to be an effective vehicle for (1) increasing the providers' awareness of the need to take better care of their own mental health requirements, (2) enriching their knowledge base about helpers stress and alternative coping responses, (3) teaching effective self-care skills. Both, the short and long term impact of training were documented.